Infective Larvae of Brugia malayi Induce Polarization of Host Macrophages that Helps in Immune Evasion - Sharma, Aditi; Sharma, Pankaj; Ganga, Laxmi; Satoeya, Neha; Mishra, Shikha; Vishwakarma, Achchhe Lal; Srivastava, Mrigank (Frontiers in Immunology, 2018)
Filarial parasites suppress, divert, or polarize the host immune response to aid their survival. However, mechanisms that govern the polarization of host MΦs during early filarial infection are not completely understood. In this study, we infected BALB/c mice with infective larvae stage-3 of Brugia malayi (Bm-L3) and studied their effect on the polarization of splenic MΦs. Results showed that MΦs displayed M2-phenotype by d3 p.i. characterized by upregulated IL-4, but reduced IL-12 and Prostaglandin-D2 secretion. Increased Arginase activity, higher Arginase-1 but reduced NOS2 expression and poor phagocytic and antigen processing capacity was also observed. M2 MΦs supported T-cell proliferation and characteristically upregulated p-ERK but downregulated NF-κB-p65 and NF-κB-p50/105. Notably, Bm-L3 synergized with host Regulatory T-cells (Tregs) and polarized M2 MΦs to Regulatory MΦs (Mregs) by d7 p.i. which secreted copious amounts of IL-10 and Prostaglandin-E2. Mregs also showed upregulated expression levels of MHC-II, CD80 and CD86 and exhibited increased antigen processing capacity but displayed impaired activation of NF-κB-p65 and NF-κB-p50/105. Neutralization of Tregs by anti-GITR+anti-CD25 antibodies checked the polarization of M2 MΦs to Mregs, decreased accumulation of regulatory B cells and inflammatory monocytes, and reduced secretion of IL-10, but enhanced IL-4 production and percentages of eosinophils which led to Bm-L3 killing. In summary, we report hitherto undocumented effects of early Bm-L3 infection on the polarization of splenic MΦs and show how infective larvae deftly utilize the functional plasticity of host MΦs to establish themselves inside the host.